Phosphoproteomic-based kinase profiling early in influenza virus infection identifies GRK2 as antiviral drug target - Emilio Yángüez (Nature Portfolio, 2018)
Influenza A virus (IAV) causes annual epidemics and development of antivirals is needed. Here, the authors perform phosphoproteomics during IAV entry and identify GRK2 as drug target, inhibition of which decreases replication of seasonal and pandemic IAV in primary human cells and animal models.